Case Report: Pharmacogenetics Applied to Precision Psychiatry Could Explain the Outcome of a Patient With a New CYP2D6 Genotype - Marcos-Vadillo, Elena; Carrascal-Laso, Lorena; Ramos-Gallego, Ignacio; Gaedigk, Andrea; García-Berrocal, Belén; Mayor-Toranzo, Eduardo; Sevillano-Jiménez, Alfonso; Sánchez, Almudena; Isidoro-García, María; Franco-Martín, Manuel (Frontiers in Psychiatry, 2022)
Precision Medicine applied to psychiatry provides new insight into the promising field of Precision Psychiatry (1). Psychotic disorders are heterogeneous, complex, chronic, and severe mental diseases (2,3). Not only does the prognosis and the course of the disease vary among patients suffering from psychotic disorders, but the treatment response varies as well(4). Although antipsychotic drugs are the cornerstone of the treatment of schizophrenia (5), many patients only partially respond these drugs (6). Furthermore, patients often experience adverse events which can lead to poor treatment adherence (7–11). Interindividual variability in drug response could be related to age, gender, ethnicity, lifestyle factors, pharmacological interactions, obesity, and genetics, all of which influence the process of drug metabolism (12–14). Commonly prescribed antipsychotics are metabolized by cytochrome P450 (CYP450) enzymes and CYP450 genes are highly polymorphic. Pharmacogenetic testing is increasingly being used to predict a patient’s drug response and could help to find the most appropriate therapy for an individual patient (15–18). In this report we describe a psychotic patient who did not receive adequate clinical follow-up and subsequently presented adverse events, which could be explained by his pharmacogenetic profile and the drug interactions resulting from the polypharmacy prescribed.